AB0516 Thrombotic Thrombocytopenic Purpura in Patients from the SLE Registry of the Spanish Society of Rheumatology (Relesser). (9th June 2015) - Lois, A.; Rúa, I.; delCampo, V.; Lόpez, F.; Galindo, M.; Calvo, J.; Hernández, I.; Belmonte, M.; Erausquin, C.; Tomero, E.; Blanco, R.; Calvo, V.; et al.
Abstract : Background: In our area, SLE patients present haematologic manifestations in approximately 70% of cases 1 . Some of these manifestations are rare so there are no large series whose analysis can provide relevant information. Objectives: To study the characteristics of patients with thrombotic thrombocytopenic purpura (TTP) in a large sample of SLE patients. Methods: SLE patients from RELESSER database were studied. We analysed the clinical and serological SLE manifestations present at the 9 domains of the British Isles Lupus Assessment Group (BILAG) activity index, all of them before, during and after TTP diagnosis until the last patient's assessment. We also studied activity (SELENA-SLEDAI) and damage (SLICC/ACR DI) indices in each one of those moments. We evaluated the treatment received, TTP recurrences and the number of deaths by this entity. Results: 3, 656 patients from 45 Rheumatology Units across Spain were studied. We found 19 cases of PTT (<1% of total). 100% were women, 94.7% Caucasian. Mean age (±SD) at diagnosis was 28.9±11.4 years. We divided the patients into 3 groups according to the chronology between diagnosis of TTP and SLE. In group 1 (G1) patients developed TTP and later SLE. In group 2 (G2) patients presented TTP and SLE simultaneously. In group 3 (G3) patients developedSLE and then TTP. According to this classification, 3, 5 and 11 patients were included in each group, respectively. At the time of TTP diagnosis the patients presented haemoglobin (g/dl) and platelets levels (mean number ± SD): In G1: 10±3.2 and 10, 667±7, 506; in G2: 7.7±2.1 and 25, 200±38, 590 and in G3: 7.4±1.8 and 22, 909±18, 387. Patients from G2, and particularly from G3, showed high SLE activity at PTT diagnosis (SLEDAI>6). Afterwards the patients maintained SLEDAI scores of 3.8±5.3 at G2 and 2.4±0.7 at G3. The number of therapy lines and the number of treatments administered was 2.8±2 and 5.4±2.9, respectively in G2, and 2.4±1.7 and 3.8±2.5 in G3, contrasting with G1 where the patients needed only 1 line ±0 of treatment and 2±1 drugs. The treatment most frecuently received by patients in G1 were glucocorticoids (GC)(100%), in G2 GC (100%), plasma exchange (PE) (80%) and cyclophosphamide (CyC)(60%); in G3 GC (81.8%), PE (72.7%) and CyC (41.8%). There were only recurrences and deaths in G3, 2 patients in each case. More detailed results of the analysis in each of the 3 groups are shown in table 1 . Conclusions: TTP is a rare event (<1%) in SLE. It can be severe and fatal. Because of this, PTT diagnosis should be suspected in all SLE patients who present anemia and thrombocytopenia and treatment should be started without delay. References: Pego-Reigosa JM et al. Analysis of disease activity and response to treatment in a large Spanish cohort of patients with systemic lupus erythematosus. Lupus. 2014. doi:10.1177/0961203314563818. Disclosure of Interest: A. Lois: None declared, I. Rúa: None declared, V. delCampo: None declared, F. Lόpez: None declared, M. Galindo: None declared, J. Calvo: None declared, I. Hernández: None declared, M. Belmonte: None declared, C. Erausquin: None declared, E. Tomero: None declared, R. Blanco: None declared, V. Calvo: None declared, E. Uriarte: None declared, P. Vela: None declared, M. Freire: None declared, J. deToro: None declared, C. Montilla: None declared, E. Raya: None declared, A. Fernández: None declared, L. Horcada: None declared, J. Pego Grant/research support from: Work supported by Spanish Society of Rheumatology, FIS/ISCIII (PI11/02857), BIOCAPS from the EU 7th Framework Programme/REGPOT-2012-2013.1 (316265), GSK, Roche, Novartis, UCB.